PEMANAFAATAN DAUN KERSEN (MUNTINGIA CALABURA) SEBAGAI BAHAN ALAMI PEMBUATAN MASKER WAJAH - Amalia, Puspa (Universitas Samudra, 2025)
Peel-off masks are masks that are easy to apply to the facial skin. The bacterium Propionibacterium acnes is one of the bacteria that cause acne. Peel-off masks are one of the preparations that can be used to maintain skin health from acne. Kersen leaves contain active compounds such as flavonoids, polyphenols, tannins, and steroids. The group of secondary metabolite compounds flavonoids and polyphenols are useful as free radical scavengers. The kersen plant (Muntingia calabura L.) is a plant that is very easy to find in the surrounding environment. The kersen plant has various benefits, one of which is for treating acne. The use of cherry leaves as a base for facial masks results in a mask preparation without a distinctive aroma, thus requiring an innovation in the cherry leaf powder mask product to enhance its fragrance. One of the ingredients that has the potential to provide a distinctive and more appealing aroma is patchouli leaves. The purpose of this community service is to determine the quality characteristics of Kersen leaf simplicia after it becomes a mask and the addition of patchouli leaves. Then to find out whether the peel-off mask is liked by the community. The Service Method is using Laboratory Experiments and interviews (instruments and questionnaires). The results showed that the preferred type of mask had a concentration of 20%, and the students were very enthusiastic during the presentation of the material.